2023
DOI: 10.1126/sciadv.ade5041
|View full text |Cite
|
Sign up to set email alerts
|

Milk-derived extracellular vesicles protect intestinal barrier integrity in the gut-liver axis

Abstract: Milk-derived extracellular vesicles (mEVs) have been proposed as a potential nanomedicine for intestinal disorders; however, their impact on intestinal barrier integrity in gut inflammation and associated metabolic diseases has not been explored yet. Here, mEVs derived from bovine and human breast milk exert similar protective effects on epithelial tight junction functionality in vitro, survive harsh gastrointestinal conditions ex vivo, and reach the colon in vivo. Oral administration of mEVs restores gut barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 67 publications
6
39
1
Order By: Relevance
“…In vitro-simulated digestion studies suggest that EVs can survive low pH and the presence of some digestive enzymes (15, 24, 25), supporting our findings that some HMEVs can survive proximal gastrointestinal digestion. However, this does not account for the observed distinct reduction in HMEV abundance in the proximal intestine.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In vitro-simulated digestion studies suggest that EVs can survive low pH and the presence of some digestive enzymes (15, 24, 25), supporting our findings that some HMEVs can survive proximal gastrointestinal digestion. However, this does not account for the observed distinct reduction in HMEV abundance in the proximal intestine.…”
Section: Discussionsupporting
confidence: 88%
“…EVs, including human milk EVs (HMEVs), carry biological information between donor and recipient cells, to confer changes in cellular function or biological activity (14)(15)(16)(17)(18)(19)(20)(21)(22). HMEVs have putative beneficial effects, as shown by a combination of in vitro and animal studies demonstrating that HMEVs promote intestinal epithelial cell proliferation (16,19,20), reduce experimental necrotizing enterocolitis (NEC), limit inflammatory (15-17, 21, 22) or non-inflammatory damage (15,19,23), promote expression of intestinal barrier proteins (21), or enhance epithelial barrier function (15,18). Collectively, the data suggest that HMEVs confer functional benefits on intestinal epithelial cells (IECs) and hold immense therapeutic promise for humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can react with the aldehyde group on allylsine, the product of LOX, to turn on its fluorescence. Subsequently, we applied TPAH to monitor fibrosis along with NASH progression using methionine- and choline-deficient (MCD) diet-fed mice as the model. - Early-stage fibrosis was observed in MCD diet-fed mice from 8 weeks onward. Notably, the administration of an LOX inhibitor for two weeks significantly reduced the fibrosis, as evident by Picrosirius Red staining and in vivo fluorescence signal after TPAH injection, suggesting the role of LOX activity in fibrosis progression.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is characterized by dyslipidemia, insulin resistance, hepatic lipid deposition, liver inflammation, and abnormal liver function. Modern research has shown that the pathological development of NAFLD is strongly correlated with the gut‐liver axis [2,3] . The trillions of gut microorganisms not only assist for absorption of nutrients, but also are critical regulators of human and animal health.…”
Section: Introductionmentioning
confidence: 99%